The conversion of a high concentration of lignin to cyclic alkanes by introducing Pt/HAP into a Ni/ASA catalyst. Issue 9 (22nd April 2020) - Qin, Shufang; Li, Bolong; Luo, Zhicheng; Zhao, Chen
Abstract : A novel strategy is demonstrated that enables the conversion of highly concentrated lignin to cyclic alkanes. Abstract : The recalcitrance of lignin with non-hydrolyzable C–O–C bonds, as well as the tendency for its phenolic fragments to polymerize into more recalcitrant polymers, leads to low-efficiency lignin deconstruction processes, such as low lignin concentrations during treatment. Herein, we developed a tandem catalytic approach for the conversion of highly concentrated lignin to stable cyclic alkanes by introducing Pt/HAP into a Ni/ASA catalyst in dodecane media. The incorporated Pt/HAP changes the simultaneous hydrogenation and hydrogenolysis of lignin on Ni/ASA into tandem reactions on a physically mixed Pt/HAP and Ni/ASA catalyst, involving the initial selective lignin depolymerization over Pt/HAP and the following hydrodeoxygenation of phenols over Ni/ASA, as evidenced by kinetic studies. In this tandem approach, the preferred initial lignin depolymerization, instead of lignin hydrogenation, originates from the strong adsorption and high C–O cleavage selectivity of lignin on the introduced Pt/HAP, as confirmed by UV-Vis, gel permeation chromatography (GPC), 2D-heteronuclear single quantum coherence nuclear magnetic resonance (2D-HSQC NMR), and catalytic tests. The rates of lignin depolymerization and the hydrodeoxygenation of depolymerized phenols are matched when the mass ratio of Pt/HAP and Ni/ASA is set at 1 : 1, allowing this approach to proceed with the highest lignin concentrations (150 g L −1 ) so far reported, with conversion to cyclic alkanes with 42 wt% yield without coke formation in dodecane at 300 °C in the presence of 6 MPa H2 . Promisingly, the developed approach may lay a solid foundation for future industrial applications relating to lignin valorization.